Antibacterial nanoagents: an emerging arsenal against bacterial persisters - Hu, Yanling; Yang, Dongliang; Yuwen, Lihui; Zeng, Guisheng (Frontiers in Microbiology, 2025)
Bacterial persisters represent a metabolically dormant or slow-growing subpopulation within bacterial communities that exhibit resistance to antibiotics. These cells are capable of resuming active proliferation upon the removal of environmental stressors, hence serving as reservoirs for recurrent infections. Extensive clinical evidence links persister cell formation with chronic infection and post-therapeutic recurrence. In this minireview, we highlight the challenges in eradicating persisters and review recent advances in nanomaterial-based antimicrobial strategies that specifically target these resilient cells. We also discuss key translational barriers impeding the clinical application of antibacterial nanoagents. By integrating these insights, we aim to provide a conceptual roadmap for the development of next-generation therapies against persistent bacterial infections.